Sustainable Agroforestry for Soil Chemical Properties Improvement and Nutrients Availability in Agriculture Landscape around Cyamudongo Isolated Forest, Rwanda - Concorde Nsengumuremyi; Eberhard Fischer; Donat Nsabimana; Marie Chantal Zaninka; JMV Senyanzobe; Bertrand Uwimana (Turkish Journal of Agriculture: Food Science and Technology)
The protected areas of Rwanda are facing various challenges resulting from the anthropogenic activities of the surrounding communities, especially in the adjacent area to Cyamudongo isolated rain forest, which results in soil degradation. Therefore, this study aims to broaden current knowledge on the impact of sustainable Agroforestry (AF) on soil-selected chemical and physical properties. To understand this, the permanent sample plots (PSPs) were established mainly in the designed four transects of four km long originating on the boundary of the Cyamudongo isolated rain forest following the slope gradient ranging from 1286 to 2015 m asl. A total number of 73 PSPs were established in the Cyamudongo study area. The Arc Map GIS 10.4 was used to design and map the sampling areas while GPS was used for localization of plots centers. Statistical significance was analyzed through R-software. The recorded soil pH means value across in Cyamudongo study area is 4.2, which is strongly acidic. The tests revealed that the soil pH, C, N, C: N ratio, OM, NH4+, NO3-+NO2-, PO43-, and CEC were significantly different in various soil depths. The pH, N, C: N ratio, CEC, NH4+, PO43-, and Al3+ showed a significant difference across land uses whereas the C and NO3-+NO2- did not show any statistical difference. All tested chemical elements showed a statistical difference as far as altitude ranges are concerned. The only NH4+, PO43-, and CEC showed significant differences with time whereas all other remaining chemical elements did not show any statistical significance. The soil pH was very strongly correlated with CEC, Mg, and Ca in cropland (CL) whereas it was strongly correlated in both AF and natural forest (NF) except for Mg, which was moderately correlated in AF. Furthermore, its correlation with K was strong in CL, and moderate in AF while it was weak in NF. Finally, the pH correlation with Na was weak in both AF and CL whereas it was negligible in NF.